Gambaran Tingkat Pengetahuan Mengenai Anastesi Spinal Operasi Sectio Caesaria pada Wanita Hamil di Klinik Ibu dan Anak - Dita Eka Saputri; Clara Valentia Josephine; Suparto Suparto; Eva Oktavia; Erma Mexcorry Sumbayak (Jurnal MedScientiae, 2022)
In Indonesia in 2019 there were 4,039,000 deliveries and 921,000 of them used cesarean delivery or around 22.8% of the total number of deliveries. The high prevalence of Sectio caserea contributes to increasing the problems caused by spinal anesthesia. Various complications that can be caused by spinal anesthesia, this requires knowledge of spinal anesthesia so that the mother is not traumatized by undergoing SC surgery. Good knowledge is needed to support postoperative healing behavior. The purpose of this study was to determine the level of insight regarding spinal anesthesia for sectio caesaria surgery in pregnant women at Clinic Maternal & Children. The research method used was quantitative descriptive, with perposive sampling technique of 96 respondents. Methods of data collection using a questionnaire and analyzed descriptively using SPSS. The results showed that the level of knowledge about spinal anesthesia for caesarean section in women at Clinic Maternal & Children was known that most of the respondents had a good level of knowledge as much as 60,4%, sufficient category as much as 30.2% and less category as much as 9,4%.